The Microflora of Gills, Gut and Skin of European Eels (Anguilla anguilla) in Lakes of Latvia - Strazdina, Vita; Terentjeva, Margarita; Valcina, Olga; Eizenberga, Inga; Novoslavskij, Aleksandr; Osmjana, Jevgenija; Berzins, Aivars (Journal of Food Science and Engineering, 2015)
The microbial contamination of fish is the most important factor in assurance of food safety. The microflora on the surface of skin, gills and gut of fish is constantly under the influence of the water environment and this may cause colonization of microorganisms on fish. The goal of this study was to evaluate the bacterial contamination level on the skin, gills and gut of the European eel (Anguilla anguilla), i.e., detecting total bacteria count (TBC) and Enterobacteriaceae counts, as well as Listeria spp. and Salmonella spp. in freshly caught fish. Among the three lakes, TBC on skin, gills and gut varied from 0.66 CFU/cm2 to 4.93 CFU/cm2, from 0.40 CFU/cm2 to 5.51 CFU/cm2 and from 0.30 CFU/cm2 to 6.37 CFU/cm2, respectively. Enterobacteriaceae count on skin, gills and gut was from 0 CFU/cm2 to 4.30 CFU/cm2, from 0 CFU/cm2 to 2.47 CFU/cm2 and from 0 CFU/cm2 to 1.72 CFU/cm2, respectively. The highest mean count of TBC on gills, skin and gut was found in samples from Sivers lake, while the lowest was in samples from Aluksne lake. Values among the lakes were significanty (P < 0.05) different. Also the highest mean counts of Enterobacteriaceae were found on gills and skin of eels from Sivers lake, but the highest count on gut was found in Usma lake. All tested samples were Listeria monocytogenes and Salmonella spp. negative. TBC and Enterobacteriaceae counts of skin, gills and gut were typical for wild fish in fresh water. Foodborne pathogens, such as Salmonella spp. and L. monocytogenes, have not been found in the present study, indicating that fish are safe for human consumption.